Aspergillus prevalence in air conditioning filters from vehicles: taxis for patient transportation, forklifts, and personal vehicles - Viegas, Carla (2018)
The frequency and importance of Aspergillus infections is increasing worldwide. This study aimed to assess the occupational exposure of forklifts and taxi drivers to Aspergillus spp. Nineteen filters from air conditioning system of taxis, 17 from forklifts and 37 from personal vehicles were assessed. Filters extract were streaked onto MEA, DG18 and in azole-supplemented media. Real-time quantitative PCR amplification of selected Aspergillus species-complex was also performed. Forklifts filter samples presented higher median values. Aspergillus section Nigri was the most observed in forklifts filters in MEA (28.2%) and in azole-supplemented media. DNA from Aspergillus sections Fumigati and Versicolores was successfully amplified by qPCR. This study enlightens the added value of using filters from the air conditioning system to assess Aspergillus spp. occupational exposure. Aspergillus azole resistance screening should be included in future occupational exposure assessments.